2006
DOI: 10.3354/meps313027
|View full text |Cite
|
Sign up to set email alerts
|

Going against the flow: retention, range limits and invasions in advective environments

Abstract: Increasing globalization has spread invasive marine organisms, but it is not well understood why some species invade more readily than others. It is also poorly understood how species' range limits are set generally, let alone how anthropogenic climate change may disrupt existing species boundaries. We find a quantitative relationship that determines if a coastal species with a benthic adult stage and planktonic larvae can be retained within its range and invade in the direction opposite that of the mean curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
241
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(246 citation statements)
references
References 50 publications
(69 reference statements)
5
241
0
Order By: Relevance
“…L diff is driven by the variability in the currents experienced by larvae spawned at different times or entrained into different coastal eddies (9,14); it could also include the effects of other larval transport mechanisms, such as shipping or fisheries. There is strong weather system-driven (23,24) and interannual variability (25,26) in the coastal current; its SD is comparable to the mean, suggesting that the upper limit on the stochastic component of larval transport should be the magnitude of the mean larval transport L adv (14). Despite these expectations, the variability in larval transport diagnosed by the model from the evolution of the cline is w3.5 times greater than the mean larval transport.…”
Section: Discussion Of the Carcinus Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…L diff is driven by the variability in the currents experienced by larvae spawned at different times or entrained into different coastal eddies (9,14); it could also include the effects of other larval transport mechanisms, such as shipping or fisheries. There is strong weather system-driven (23,24) and interannual variability (25,26) in the coastal current; its SD is comparable to the mean, suggesting that the upper limit on the stochastic component of larval transport should be the magnitude of the mean larval transport L adv (14). Despite these expectations, the variability in larval transport diagnosed by the model from the evolution of the cline is w3.5 times greater than the mean larval transport.…”
Section: Discussion Of the Carcinus Systemmentioning
confidence: 99%
“…Neutral genotypes that are introduced or arise elsewhere in the range will tend to be lost as deceased adults are replaced by migrants from farther upstream. The upstream edge of the species domain can retain new genotypes because there is little or no external immigration from farther upstream (14,15), and so the population must be maintained by local production. This upstream region will export migrants containing these genotypes downstream, which will, in time, spread the genotype throughout the entire species' range.…”
mentioning
confidence: 99%
“…Species inhabiting the deeper waters over the continental shelf release larvae directly into the more energetic and less variable flow over the continental shelf and seaward of the coastal boundary layer (Largier, 2003). Larvae released into a mean current will drift downstream from their release site, most will settle downstream of their parents, and if this process goes unchecked, the species will go extinct from the upstream edge of its distribution to the downstream Shanks and Eckert, 2005;Byers and Pringle, 2006). This is known as the "drift paradox" (Müller, 1982) and is a problem for all species with pelagic larvae; however, given the stronger flow in offshore waters, it may be particularly severe for species living away from shore on the continental shelf.…”
Section: Organisms With Pds ͻ Half a Day Organisms Withmentioning
confidence: 99%
“…This is known as the "drift paradox" (Müller, 1982) and is a problem for all species with pelagic larvae; however, given the stronger flow in offshore waters, it may be particularly severe for species living away from shore on the continental shelf. Modeling by Byers and Pringle (2006) suggested that spreading spawning over several seasons, short PD, and prodigious larval production might mitigate larval washout. Contranatant spawning migrations have also probably evolved to "solve" this problem (Cushing, 1975).…”
Section: Organisms With Pds ͻ Half a Day Organisms Withmentioning
confidence: 99%
“…Advective dispersal is not limited to streams but is also important along coastlines (Gaines et al 2003;Byers and Pringle 2006) and in the gut (Ballyk and Smith 1999;O'Brien and Gordon 2011), and it has parallels to climate change (Potapov and Lewis 2004). Our model captures two primary effects of drift: shifted abundance distributions (e.g., Anderson et al 2005Anderson et al , 2006Pachepsky et al 2005) and boundary mortality (washout; e. g., Müller 1982;Speirs and Gurney 2001;Lutscher et al 2010).…”
Section: Theory Of Streams and Advective Habitatsmentioning
confidence: 99%